Trade with benefits: New insights on competition and innovation - JaeBin Ahn; Hyoungmin Han; Yi Huang (Graduate Institute of International and Development Studies, 2018)
This paper examines how Korea's import and export linkages with China affect the innovation outcomes of Korean manufacturing firms. Using our automated algorithm, we match Korean patent data to KIS-Value firm data from 1996 to 2015. We find that rising import and export with China lead to more patent applications by Korean manufacturing firms, with the positive impact particularly driven by large or public firms compared to SMEs or private firms. Most importantly, all of these results hold only in those sectors with higher quality products than Chinese products, shedding lights on reconciling recent empirical studies that found conflicting evidence on "Schumpeterian force" and "escaping competition."
Keywords: F14; F16; O34; 330; Competition; Innovation; China Shock; Schumpeterian Force; Escaping Competition